Hubungan Interteks Konsep Pengorbanan Ibu Pada Puisi “IBU” Karya Mustofa Bisri dan Lagu “IBU” Karya Iwan Fals - Rizky Ardiansyah; Yoga Pranaseta Wibowo; Acmad Humam Fadil; Yosi Wulandari (Jubah Raja : Jurnal Bahasa, Sastra, Dan Pengajaran, 2023)
This study aims to determine the concept of a mother's sacrifice which is narrated in the poem "Ibu" by Mustofa Bisri and the song "Ibu" by Iwan Fals which has a background of the great struggle of a mother. The method used in this study is a descriptive-comparative method and uses an intertextual approach. The result of the analysis of these two works is the fact that the struggle of a mother is great and how important her role is in the development of children so that her image in a child is always closely related to love, struggle and sacrifice.Keywords – Sacrifice, Mother, Intertext.